Cracking of 5Cr steel tee-pipe during start-up operation in heavy oil upgrade refinery. (November 2017) - Yoon, Kee Bong; Byun, Chul Hyun; Nguyen, Tuan Son; Yu, Jong Min; Jeon, Gyu Min
Abstract: During the start-up operation of an HOU refinery plant, leaking through a crack at the top of a T-pipe was found in a hydrocracking process. Various kinds of metallurgical inspections of the failed T-pipe were performed in order to find the cause of cracking e.g., metallography, fractography, hardness measurement, EDS analysis and hydrogen concentration measurement. Since thermal loading in the T-pipe was usually higher during the start-up operation than under steady operations, a system load analyses of the pipe was conducted. Detailed finite element analysis of the T-pipe was also conducted to identify high stress locations and to assess the stress intensity factor of the crack partly penetrated the T-pipe. The 5Cr T-pipe steel satisfied the chemical composition requirements for ASTM A234 but the tensile strength and hardness were significantly higher than recommended in the standard, which made the pipe steel vulnerable to a hydrogen environment formed by the feed inside of the pipe. The cracking started from the inclusions near the inner surface of the pipe and grew due to the hydrogen effect. Inspection results supporting this argument are explained. And recommendations for preventing similar cracking failures were made. Highlights: Leaking at T-pipe occurred during start-up operation of a refinery plant. Cracking can occur at very low stress locations if hydrogen damage is involved. 5Cr steel with high hardness/strength made it vulnerable to hydrogen damage. Inclusions (Al2 O3, SiO2 ) near the inner surface may act as hydrogen crack initiation locations. Hydrogen charging as a result of SCC reaction can cause hydrogen cracking.